Risk attitudes and household consumption behavior: Evidence from China - Xie, Xin; Tong, Zefeng; Xu, Shulin (Frontiers in Public Health, 2022)
Risk attitude is a vital component of public mental health. Thus, the public should be guided to fully comprehend risks to improve public mental health. Using panel data from China Household Finance Survey (CHFS) in 2017, this study examined the impact of risk attitudes on household consumption behaviour by constructing a micro-econometric model. Results suggest that risk attitude can promote household consumption, with multiple robustness tests supporting this conclusion. In addition, after dividing the consumption types into subsistence consumption, development consumption and enjoyment consumption, we show risk preference promotes all three types of consumption and has the greatest impact on enjoyment consumption. Concurrently, risk neutrality can promote household survival consumption, but its promotion effect is smaller than that of risk preference. Moreover, risk aversion have an inhibitory effect on total consumption behaviour, but this inhibitory effect does not show heterogeneity for different consumption behaviours. Heterogeneity analysis found that for male households, risk attitude remains an important factor in consumption behaviour. When men’s risk attitude is more risk averse, it can promote more survival consumption, whereas women’s risk attitude is more risk averse. With increasing age, risk attitude remains a crucial factor in the occurrence of consumer behaviour. However, education level has no bearing on the effect of risk attitude on household consumption behaviour. This research holds theoretical and practical significance for improving public mental health, optimising residents’ consumption structure, and achieving high-quality economic development.